Reimagining Teacher Professional Development to Link Theory and Practice - Abror, Sirojuddin; Purnomo; Hardinanto, Eko; Mintarsih, Mimin; Mutrofin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
Importance development professional teacher in increase quality education No can viewed adjacent eyes. However, even though various training programs has applied, still there is gap significant between the theory taught in training and practice carried out in class. This is show the need approach newer one​ effective in development teacher professionalism. Research This aiming For explore ways For bridge gap between theory and practice in teacher training, as well as evaluate effectiveness approach collaborative and use technology in increase quality teaching. Methods used​ in study This is studies literature and analysis policy, with dig various study past and experience relevant field.​ Data is collected through study to various articles, books and reports study related development professional teacher. Research result show that teacher training that combines approach collaborative, such as lesson study and community learn, more effective in increase teacher understanding and skills. In addition that, integration technology in training can expand access and provide experience more learning​ flexible as well as adaptive. Support strong institutions, including​ time For collaboration and provision source power, also plays role important in success training. Research This recommend the need design more training​ holistic and based context local, as well as focus on reflection and evaluation sustainable For ensure success term long in development professional teacher.